“Ethno-Religious Minorities”, in The Historiography of Medieval Portugal (c.1950-2010) - Barros, Maria Filomena Lopes de (2012)
The Portuguese Medieval historiography (c. 1950-2010) about the ethno-religious minorities does not appear to bring about (contrary to Spain) any centrality in the discourse on Portuguese identity, on the one hand, just as it also does not comport, on the other, a reflection especially oriented towards the emerging heuristic presuppositions. In this sense, the relative “marginality” of the study of the Minorities contrasts with the multiplication of centres and publications devoted to the Jews and Muslims (Mudejares) in neighbouring Spain, And, yet, both minorities also integrated the medieval society of the Portuguese realm, and both suffered the religiocide policy decreed by King Manuel I in December 1496. In general terms, moreover, the Portuguese historiography of the last 50 years is marked by another asymmetry, this one achieved internally, between the works devoted to Jews and to Muslims. The progressive projection of the Jew, as a historiographical material, is countered by the near invisibility of the “Moor” (a term that, in the Middle Ages, designated, in fact, the Muslim in the Iberian context). The terms of the Minorities historical analysis suffered a turnover point in the decade of the 1990’s, and, in the 2010’s decade, new research proposals are being prepared for the study of both minorities.